ANALISIS WACANA KRITIS STRATEGI POLITIK PENGGUNAAN BAHASA DALAM PIDATO PRESIDEN SUSILO BAMBANG YUDHOYONO - Endang Sumarti (LITERA, 2010)
This study on the political strategy in the language use in Susilo BambangYudhoyono’s speeches is focused on the language behaviors. The data were collected from the internet sources containing his speeches in several occasions with regard to political policies during his presidency. The data were analyzed using the critical discourse analysis approach. The results show that his political strategy in the language use is reflected in the uses of words, sentences, and figures of speech. The language use helps public understandings of the conditions that Indonesian people are now facing and supports his presidency. From the language praxis, his political strategy in the language use is relevant to language behaviors in general.